State violence and persistent atrocities involving indigenous peoples in Brazil - Almeida, Bruno Rotta; Sallet, Bruna Hoisler (Revista do Instituto Histórico e Geográfico Brasileiro, 2023)
The article studies the violations perpetrated against indigenous peoples in Brazil. We seek to inquire to what extent the Brazilian State contributes to the genocide of indigenous peoples. The relevance of the research is due to the ongoing threatening posture of the State, which legitimizes human rights violations of indigenous peoples. The article is divided into five parts. Firstly, we track the development of knowledge about the indigenous issue. Secondly, we analyze the landscape of indigenous rights in the international and national legal-normative context. Thirdly, we aim to show the importance of memory as a category for studying atrocities. Fourthly, we analyze data and information about cruel acts practiced during the civil- military dictatorship. Lastly, we point to the key players in the state violence, and show how vulnerable indigenous peoples are in the face of continued cruel behavior on the part of the state. Our methodology is based on the deductive method, bibliographic review and documentary research.